Coronal pulpal height changes in type 2 diabetics: A cross-sectional pilot study utilizing panoramic radiographs - Nisha Kumaravel; Saramma Mathew Fenn; Mathew Jacob (Wolters Kluwer Medknow Publications, 2024)
Background: Type 2 diabetes mellitus can significantly affect oral health, potentially leading to morphological changes in the dental pulp. Aim: The study aims to assess and compare the coronal pulpal height of the maxillary canine and mandibular first molar between type 2 diabetics and nondiabetics by utilizing panoramic radiographs. The coronal pulpal height of the maxillary canine and mandibular first molar between individuals with type 2 diabetes and those without diabetes using panoramic radiographs. Settings and Design: The study was conducted as a retrospective cross-sectional study in the Department of Oral Medicine and Radiology. Materials and Methods: Coronal pulp heights of the maxillary canine and mandibular first molar were measured in 100 orthopantomograms (OPGs) from the diabetic and nondiabetic groups, along with the corresponding same-day random blood glucose levels in the diabetic group. Statistical Analysis: A t-test was used to compare blood glucose and coronal pulpal height between the two groups and Pearson correlation coefficients to assess relationships between blood sugar level and coronal pulpal height. Results: In the maxillary canine, the diabetic group had a coronal pulpal height of 3.50 mm, while the nondiabetic group had 2.55 mm, with P = 0.002 and 0.047, respectively. Positive correlations between blood glucose levels and the maxillary canine's coronal pulpal height (1.000), with a weaker correlation with the mandibular first molar's height (0.116), were also observed. A negative correlation (−0.256) was observed between the coronal pulpal heights of the maxillary canine and mandibular first molar. Conclusions: The diabetic group showed increased coronal pulpal height in the maxillary canine compared to the nondiabetic group. There was a positive correlation between blood glucose levels and the pulpal height of the maxillary canine, with a weaker correlation for the mandibular first molar. Clinical Significance: This study highlights the critical role of early oral health monitoring for individuals with type 2 diabetes, enabling dental professionals to detect potential signs of undiagnosed diabetes through radiographic assessments.